Assessment of effects of mouthwash by Buccal Micronucleus Cytome Assay: a Preliminary Study - HERNANDES, Karolina Cardoso; SILVA, Camila Alves da; SCHMIDT, Vanessa Kristine de Oliveira; BOEIRA, Jane Marlei (Revista Eletrônica Científica da UERGS, 2016)
ABSTRACT: Mouthwashes are the most common antiseptic used for buccal hygiene. However, some studies have shown that these compounds containing alcohol can induce genotoxic and carcinogenic effects. The human buccal micronucleus cytome assay (BMCyt) has been used widely to investigate biomarkers for DNA damage, cell death, cytockinesis defects and basal cell frequency in buccal cells. Thus, the aim of this study was to assess whether the mouthwashes could induce genetic damage in exfoliated cells of the buccal epithelium by BMCyt. Sixty individuals participated of this study, divided in two groups: one, exposed to mouthwashes (n = 30), and another, not exposed (control group; n = 30). Nuclear damage (micronucleus and nuclear buds), incomplete cytokinesis (binucleated cells), cell death (condensed chromatin, karyorrhectic, pyknotic and karyolytic cells) and basal cells were evaluated in epithelium cells using image analysis at x1,000 magnification. The results showed a significant increase of nuclear buds, pyknotic and basal cells in exposed group. We observed that the composition of alcoholic products can be related to the micronucleus and nuclear bud cells frequencies, according to the following order: Listerine® > Colgate® > Oral B®. However, studies with a larger numbers of individuals are need to support the preliminary findings presented here. RESUMO: Os enxaguatórios bucais são os antissépticos mais utilizados para a higiene bucal. No entanto, alguns estudos demonstraram que estes compostos que contém álcool podem induzir efeitos genotóxicos e carcinogênicos. O ensaio de micronúcleos em células da mucosa bucal (BMCyt assay) de humanos tem sido amplamente utilizado para investigar biomarcadores para avaliação de danos no DNA, morte celular, defeitos na citocinese e frequência de células basais em células bucais. Assim, o objetivo deste estudo foi avaliar se os enxaguatórios poderiam induzir danos genéticos em células esfoliadas do epitélio bucal pelo ensaio BMCyt. Participaram do estudo 60 indivíduos, divididos em dois grupos: um grupo exposto aos enxaguatórios (n = 30) e outro não exposto (grupo controle, n = 30). Os danos nucleares (micronúcleos e brotos nucleares), citocineses incompletas (células binucleadas), morte celular (células com cromatina condensada, cariorréxis, picnóticas e cariolíticas) e células basais foram avaliados em células de epitélio usando análise de imagem com aumento de 1.000x. Os resultados mostraram um aumento significativo de células com brotos nucleares, picnóticas e basais no grupo exposto. Observamos que a composição de enxaguantes contendo álcool pode estar relacionada às frequências de micronúcleos e de células com brotos nucleares, de acordo com a seguinte ordem: Listerine®> Colgate®> Oral B®. No entanto, estudos com um maior número de indivíduos são necessários para sustentar os resultados preliminares aqui apresentados.